Co-modification with MSC membrane and PDA prevents Fe3O4-induced pulmonary toxicity in mice via AMPK-ULK1 axis. (15th October 2021) - Yao, Hua; Yan, Jun; Shao, Pu; Wang, Yuzhuo; Liu, Tianxin; Jiang, Jinlan; Liu, Te
Graphical abstract: Flow diagram of the animal experiment. Abbreviations : MSC, Mesenchymal stem cell; PDA, polydopamine; PBS, phosphate buffer solution; BALF, bronchoalveolar lavage fluid; ELISA, enzyme linked immunosorbent assay; H&E, hematoxylin-eosin; IHC, immunohistochemistry; TEM, transmission electron microscopy. Highlights: MSCM and PDA co-modified Fe3 O4 reduced autophagy and apoptosis of mouse lung tissue. It prevents Fe3 O4 -induced pulmonary toxicity by reducing AMPK-ULK1 axis activation. MSCM and PDA co-modification can protect lung tissue from oxidative stress damage. The co-modification way can improve biocompatibility and application of Fe3 O4 NPs. Abstract: Fe3 O4 nanoparticles are widely used in the diagnosis and treatment of diseases due to their superparamagnetism, but their toxicity in vivo, which can result in apoptosis or autophagy, cannot be ignored. It has been reported that polydopamine (PDA) modification can reduce the toxicity of Fe3 O4 and increase its biocompatibility. However, more research is warranted to further improve the modification method. We therefore developed a new method to coat Fe3 O4 @PDA nanoparticles with the mesenchymal stem cell membrane (MSCM) and evaluated the toxicity of the modified particles in the lungs of mice. We found that the MSCM modification significantly reduced lung injury induced by Fe3 O4 particles in mice. Compared with Fe3 O4 @PDA nanoparticles, co-modification with MSCM and PDA significantly reduced autophagy and apoptosis in mouse lung tissue, and reduced activation of autophagy mediated by the AMPK-ULK1 pathway axis. Thus, co-modification with MSCM and PDA prevents Fe3 O4 -induced pulmonary toxicity in mice by inhibiting autophagy, apoptosis, and oxidative stress.